2011
DOI: 10.1016/j.clinph.2010.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment for EEG-based neonatal seizure detectors

Abstract: ObjectiveThis study discusses an appropriate framework to measure system performance for the task of neonatal seizure detection using EEG. The framework is used to present an extended overview of a multi-channel patient-independent neonatal seizure detection system based on the Support Vector Machine (SVM) classifier.MethodsThe appropriate framework for performance assessment of neonatal seizure detectors is discussed in terms of metrics, experimental setups, and testing protocols. The neonatal seizure detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 20 publications
2
122
2
Order By: Relevance
“…The sensitivity as a function of the positive predicted value is sometimes called precision-recall (PR) curve (Temko et al, 2011). The sensitivity and positive predicted values are computed as (1) (2) where N expert is the total number of expert's marks (detected plus undetected by the automatic detector), N dem is the number of detected expert's marks, N auto is the total number of automatic detections (true plus false positives), and N tp is the number of true positive automatic detections.…”
Section: Performance Metricsmentioning
confidence: 99%
“…The sensitivity as a function of the positive predicted value is sometimes called precision-recall (PR) curve (Temko et al, 2011). The sensitivity and positive predicted values are computed as (1) (2) where N expert is the total number of expert's marks (detected plus undetected by the automatic detector), N dem is the number of detected expert's marks, N auto is the total number of automatic detections (true plus false positives), and N tp is the number of true positive automatic detections.…”
Section: Performance Metricsmentioning
confidence: 99%
“…Finally, the NFM based estimate of η was combined with aEEG amplitude using a trained LDC, with pre-processing and post-processing stages, to form a simple SDA. This SDA was tested on the full database of neonatal EEG and assessed with the AUC, seizure detection rate and false alarms per hour metrics [31]. Two clinically relevant measures of a SDA are the ability of the SDA to discriminate seizure from nonseizure neonates when applied to long duration EEG recordings and the ability of the SDA to accurately estimate the seizure burden of the neonate.…”
Section: Resultsmentioning
confidence: 99%
“…There are many issues with comparing the performance of SDAs [31]. Differences in performance metrics and neonatal EEG databases make any comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no standard for reporting detection performance, two complementary procedures are gaining wide acceptance. These methods are the event-based and the time-based detection methods [19,56]. Temko et al [56] correctly concluded that the best way to report the performance of a seizure detector is to include a number of different, but complementary, measures.…”
Section: Detection Performance Comparison With Greene's Algorithmmentioning
confidence: 99%